2017
DOI: 10.1016/j.acap.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Responding to ACEs With HOPE: Health Outcomes From Positive Experiences

Abstract: This article introduces a framework called "HOPE: Health Outcomes From Positive Experiences." The HOPE framework focuses on the need to actively promote positive childhood experiences that contribute to healthy development and well-being, as well as prevent or mitigate the effect of adverse childhood experiences and other negative environmental influences. Key positive childhood experiences fall within 4 broad categories: being in nurturing, supportive relationships; living, developing, playing, and learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 42 publications
7
132
0
2
Order By: Relevance
“…These results are consistent with a recent study of the intersection between youth who ran away from home and those who experienced homeless, showing that those who had both run away and been homeless were at greater odds of mental health problems than either group alone (those who ran away had intermediate odds). 32 Overall, our findings affirm the protective nature of caregivers and families [33][34][35][36][37] and underscore the importance of ensuring that youth who have suffered adversity (e.g., maltreatment, neglect, or family dysfunction) are protected from becoming separated from supportive family members when faced with evictions or unsafe housing, humanitarian crises, disasters, war, or refugee/immigration policies that simultaneously threaten the integrity of families and the homes that allow health to thrive.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These results are consistent with a recent study of the intersection between youth who ran away from home and those who experienced homeless, showing that those who had both run away and been homeless were at greater odds of mental health problems than either group alone (those who ran away had intermediate odds). 32 Overall, our findings affirm the protective nature of caregivers and families [33][34][35][36][37] and underscore the importance of ensuring that youth who have suffered adversity (e.g., maltreatment, neglect, or family dysfunction) are protected from becoming separated from supportive family members when faced with evictions or unsafe housing, humanitarian crises, disasters, war, or refugee/immigration policies that simultaneously threaten the integrity of families and the homes that allow health to thrive.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to trauma-informed care, advocacy is needed for "resilience-informed care" that incorporates protective factors both in clinical practice and social policies. 37,53 Traditionally, policy work and medical care are focused on identifying and treating problems. Less attention is paid to what is going well, particularly in contexts of known risk, such as homelessness or ACEs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sege and colleagues (Sege and Browne 2017; developed and applied a framework called Health Outcomes for Positive Experiences (HOPE) in their research on childhood adversity and found that positive childhood experiences had long-term, salutogenic effects . In line with these findings, Crandall et al, (2019) conducted an on-line study of counter-ACEs (defined as exposure to positive experiences in childhood) and their role in predicting adult health behaviors and outcomes.…”
Section: Strengths Protective Factors and Resiliencementioning
confidence: 99%
“…In addition to trauma-informed care, advocacy is needed for "resilience-informed care" that incorporates protective factors both in clinical practice and social policies. 35,50 Traditionally, policy work and medical care are focused on identifying and treating problems. Less attention is paid to what is going well, particularly in contexts of known risk, such as homelessness or ACEs.…”
Section: Discussionmentioning
confidence: 99%